Alternative butanol/gasoline and butanol/diesel fuel blends: An analysis of the interdependence between physical-chemical properties by a multivariate principal component analysis model. Issue 5 (August 2020) - Brandão, Luiz Filipe Paiva; Braga, Jez Willian Batista; Suarez, Paulo Anselmo Ziani
The use of butanol as an oxygenated component in blends with fossil fuels has recently been recognized by the industry as a promising and green alternative for automotive use, being subject of several recent studies. In this work, the interdependence between important physical-chemical properties of butanol/gasoline and butanol/diesel fuel blends was investigated using a multivariate principal component analysis model. The model dataset was based on laboratorial results of density, kinematic viscosity, distillation, vapor pressure, octane rating, anti-knock index, flash point and cetane number in a total of 48 blends, the variables of which were transformed to principal component analysis matrix representations, pre-processed and then analyzed. A good coherence was observed between the experimental results in laboratory and those derived from the principal component analysis models, evidencing important physical-chemical changes in blends' properties due to the butanol addition. Principal component analysis scores and loadings plots could provide an intuitive and comprehensive data visualization. Butanol/gasoline fuel blends showed an overall increase in density, octane rating and higher distillation temperatures from the initial boiling point to T60 (temperature of the 60% distilled volume) and reduction of the distillation temperatures from T70 to the final boiling point. An absolute reduction in values of all properties was observed for butanol/diesel fuel blends, especially for initial distillation temperatures from initial boiling point to T35, T98, final boiling point and flash point, whereas the reductions for density, kinematic viscosity and cetane number were less intense. Total variances of up to 92.50% and 94.14% were explained by the proposed principal component analysis model, depending on the blends matrix and butanol isomer composition.